Use of botulinum toxin as a potetial treatment of chronic migraine: A literature review (Research, Society and Development, 2023)
Chronic migraine is a complex neurological pathology that causes disability and impacts on the quality of life of those affected. The failure of prophylactic treatment in a high percentage of patients increased the need to seek adequate treatment. In 2010, the Food and Drug Administration approved the use of botulinum toxin type A for the treatment of chronic migraine in patients who have not responded adequately to or are intolerant of commonly used medications. Therefore, the present study aimed to describe a literature review, with an integrative approach, presenting the main benefits of using botulinum toxin as a potential treatment for chronic migraine, in addition to presenting the mechanism of action and aspects related to its effectiveness in reducing levels of pain promoted by migraine. With regard to the search for articles, this was carried out from the databases: PubMed, SciELO and Lilacs, through the application of inclusion and exclusion criteria, where 30 materials published between the years 2014 to 2022 were selected, written in Portuguese, English or Spanish. The studies revealed that botulinum toxin is effective in reducing the frequency and severity of headaches in patients with chronic migraine, both in the short and long term. It is concluded that botulinum toxin is a safe and effective method for the prophylaxis and treatment of chronic migraine, thus proving its mechanism of action and aspects related to its effectiveness in reducing the levels of pain caused by migraine, which can significantly improve the outcome. management of this highly disabling disorder.